Resource Allocation in C-RAN with Hybrid RF/FSO and Full-duplex Self-Backhauling Radio Units - Bayati, Seyedrazieh; Darabi, Mostafa; Mostafa, Ayman; Lampe, Lutz (IEEE International Conference on Communications (2003), 2021)
This paper considers the downlink of a cloud radio access network (C-RAN) consisting of a central processor (CP) and a network of connected radio units (RUs). We propose a novel resource allocation solution for the scenario with full-duplex (FD) self-backhauling RUs connected through hybrid radio-frequency (RF)/free-space optical (FSO) links to the CP for improved network throughput. This enables us to study the feasibility of the FD mode in terms of required self-interference cancellation to outperform the benchmark half-duplex hybrid RF/FSO transmission. Since the derived optimization problem for the design of the linear precoders and quantizers subject to the fronthaul capacity, zero-forcing, and power constraints, is non-convex and intractable, we develop an algorithm to solve it via an alternating optimization approach. In the simulation results, the proposed hybrid RF/FSO policy is assessed in terms of achievable rate, and we highlight the parameter range for which FD transmission is more rewarding than the time-division approach, under different weather conditions and selected RF bandwidth.